Проблема індоєвропейської прабатьківщини у контексті останніх лінгвістичних досліджень - Павленко, Ю.В. (Археологія, 1994)
Індоєвропейська проблема є традиційною для археології та мовознавства. У статті на підставі сучасних досліджень обгрунтовується гіпотеза про формування індоєвропейської спільності у Передкавказзі та Припонтійських степах до доби неоліту. 1980-е гг. ознаменовались появлением ряда фундаментальных исследований в области сравнительно-исторического языкознания, требующих обобщающего историко-археологического осмысления. Их анализ в контексте археологических разработок приводит к выводу о формировании праиндоевропейской общности на стадии перехода к мезолиту в Кавказско-Крымских предгорьях и в сопредельных с ними степных районах. Эта гипотеза объясняет наличие изначального родства индоевропейских языков как с уральскими и алтайскими, так и с картвельскими. В ее контексте решается и проблема ранних связей древних индоевропейцев с прасемитами и носителями прасеверокавказских (древнейших махоазийских) диалектов. Последнее объясняется инфильтрацией с юга неолитических земледельческо-скотоводческих групп. Some fundamental studies in the field of comparative-historical linguistics appear in 1980s. They require generalized historico-archaeological comprehension. Their analysis in the aspect of archaeological developments permits a conclusion to be made on formation of fore-Indo-European community (as an ethnolinguistic continuity) at the stage of transition to mesolith in the Caucasus-Crimean mountains and in steppe regions contiguous with them. This hypothesis explains the presence of initial affinity of Indo-European languages both wilh Ural, Altai languages and with Cartvel ones. In this aspect the problem of early contacts of ancient Indo-Europeans with fore-Semites and carriers of fore-North-Caucasian (ancient Minor-Asian) dialects is discussed. The latter is explained by infiltration of neolithic agricultural and cattle-breeding groups from the south.